Obowiązek rolniczego wykorzystywania określonych gruntów rolnych w PRL - Pawlak, Wiktor (Wydział Prawa i Administracji UAM, 1983)
The constitutional principle of a proper utilization of land as a national property is reflected, among others, in a duty of agricultural utilization of farmlands and land re-cultivated f'or agricultural purposes. Two structures of subjects can be defined upon characterizing this regulation: the State — owners of agricultural estates, and owners of these estates — all non-owners. The statutory duty of agricultural utilization of farmlands and lands re-cultivated for agricultural purposes is a part of the structure: the State — owners of agricultural estates. According to the valid legal rules, this duty does not have to be substantiated in a form of administrative decision but directly creates the obligation for owners (possessors) to perform generally defined real actions on specified cultivable lands. Fulfillment of this duty is a subject of control perfomed by a primary State's administrative agency in a period of plants' vegetation. The statutory duty on owners (possessors) of specified cultivable lands- of utilizing them in agricultural way is related to the right of State administrative agencies to control its fulfillment. Thus the duty becomes an element of potential relation under administrative law of the basic character in the aspect of substantive law. Content of the duty being an order of running effective vegetable production imposes itself in a way on that part of allowed behavior of owners (possessors) which consists in taking up vegetable production. In case of observing any action contrary to the ordered activities State administrative agencies are competent to levy measures of execution. In this way a potential relation under law and execution can foe defined, it is one of the types of a relation under administrative law.
A duty of agricultural utilization of specified cultivable lands in the Polish People's Republic